(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2003)
Aftereffects of high temperature on the kinetics of slow induction of chlorophyll a fluorescence were studied in Chlorella. Heating of alga at the temperature over 45°C caused decrease of induction curve parameters P and M. Changes of these parameters indicated a suppression of photosystem 2 activity. Photosystem 1 was more stable to the high temperature effect. The results suggest that an algae thermosensitivity may be evaluated by changes in the induction curves of slow fluorescence in the preheated objects. The pattern of changes in kinetic curves may indicate disturbances in particular sites of photosynthetic electron transport chain.